Peran Pendidikan Karakter Dalam Membangun Kepribadian Pelajar di SMAN I Salem - Achmad, Fatoni; Srinawati, Risna; Nisa, Dinda Khoirun (MUNAQASYAH : Jurnal Ilmu Pendidikan dan Pembelajaran, 2019)
This study aims to determine the role of character education in building the personality of students especially at Salem SMA I Salem. The method used in the study is qualitative. This type of research is field research, while the data collection technique uses interviews and documentation. The results of the study indicate that: a. The existence of school activities that functioned for the formation of student character, the role of character education can be found in organizations and in extracurricular activities organized by SMA N 1 Salem b. The relevance of character education in building the personality of students, character education is very necessary to maintain the quality of the personality of students by providing understanding, direction, and assistance so that students display a good personality.